God, the good, and the spiritual turn in epistemology - Ceglie, Roberto Di (Cambridge : Cambridge University Press, 2023)
In this book, Roberto Di Ceglie presents a historical, theological, and epistemological exploration of how commitments to God and/or the good create the ideal conditions for acquiring knowledge. Di Ceglie challenges the common notion that to gain knowledge, one must always be prepared to replace one's convictions with beliefs that seem to be proven. He defends a broader perspective, historically exemplified by prominent Christian thinkers, in which believers are encouraged to remain committed to God and related beliefs, even in the face of evidence that appears to contradict those beliefs.
Includes bibliographical references and index.
Keywords: Religion; Knowledge, Theory of (Religion).